“Estudio técnico y económico de dos tecnologías de potabilización de agua impulsadas por energías renovables en el municipio de Manaure – La Guajira” (2020)
Water, due to its value and importance for humanity, is considered the most valuable resource available. Colombia has undergone major changes in terms of treatment, management and distribution of the resource, seeking ways to adapt to meet current and future demand in the face of critical situations of scarcity that the most vulnerable populations in the country are facing, a particular case is the municipality of Manaure - La Guajira. Drought problems, low annual rainfall volumes and overexploitation of water resources have led to the creation of strategies and research projects in the municipality of Manaure. This gives way to the development of the objective of our work, which is to compare the technical and economic feasibility of two water purification technologies powered by renewable energies in the municipality of ManaureGuajira; The aim is to find an optimal solution to obtain water suitable for human consumption. This project generates benefits in terms of the population of the municipality of Manaure who will be positively affected at an economic, sanitary and environmental level, therefore there will no longer be a shortage of water in the municipality, since the water supply is inexhaustible and this will allow that its population supports its consumption every day in excellent conditions for a better lifestyle.